2013
DOI: 10.1007/s13277-012-0616-8
|View full text |Cite
|
Sign up to set email alerts
|

Improved efficacy of therapeutic vaccination with viable human umbilical vein endothelial cells against murine melanoma by introduction of OK432 as adjuvant

Abstract: Vaccination with xenogeneic or syngeneic endothelial cells targeting tumor angiogenesis is effective for inhibiting tumor growth. OK432, an effective adjuvant, was mixed with viable human umbilical vein endothelial cells (HUVECs) to prepare a novel HUVECs-OK432 vaccine, which could have an improved therapeutic efficacy. In this study, HUVECs-OK432 was administrated in mice by subcutaneous injection in a therapeutic procedure. The results showed that a stronger HUVEC-specific Abs and cytotoxic T lymphocyte immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Therefore, inhibition of angiogenesis is currently being studied as a new anticancer therapy. Since the first vaccine targeting tumor angiogenesis was reported, proliferative HUVECs as a vaccine to induce antitumor immunity has been studied in several in vivo tumor models (5)(6)(7)(8)17,26). However, further investigation is required before the HUVEC vaccine can be used clinically, and the antitumor effect has not been studied previously in esophageal carcinoma.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, inhibition of angiogenesis is currently being studied as a new anticancer therapy. Since the first vaccine targeting tumor angiogenesis was reported, proliferative HUVECs as a vaccine to induce antitumor immunity has been studied in several in vivo tumor models (5)(6)(7)(8)17,26). However, further investigation is required before the HUVEC vaccine can be used clinically, and the antitumor effect has not been studied previously in esophageal carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…It has been well established that angiogenesis forms the basis of tumor development and metastasis; thus, suppressing tumor-associated angiogenesis has become a favorable strategy for the treatment of cancer (4). Active immunization with a whole endothelial cell vaccine can control tumor size and metastasis by restraining tumor angiogenesis in mice (5). Human umbilical vein endothelial cell (HUVEC) vaccines have been effective in anti-angiogenesis immunity against melanoma, glioblastoma, colorectal cancer and hepatocellular carcinoma (5)(6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of six mice of the three immunized groups in the prophylactic strategy were administered with separate vaccines every week for four consecutive weeks, and serum was collected every week following initial immunization. The anti-H22 antibodies present in the serum were evaluated using an ELISA, as described previously ( 16 ). Briefly, 96-well flat-bottomed ELISA plates were coated with 10 ”g/well of whole H22 cell lysates protein.…”
Section: Methodsmentioning
confidence: 99%
“…Our results showed that OK432 could act as an effective adjuvant to assist HUVEC to elicit a more obvious inhibition than HUVEC alone. 13 However, all the mice eventually died because of the tumor attack, suggesting that the antitumor efficiency of HUVEC-OK432 vaccine was not completely satisfactory. This indicated that the strategy of using appropriate adjuvant to enhance the antitumor efficiency of HUVEC vaccine is feasible but need further optimization.…”
mentioning
confidence: 99%